Coping strategies and brain activity in table tennis players faced with discrepancies between predicted and actual outcomes - Wang, Y.; Zhao, Q.; Shan, X.; Lu, Y. (Journal of Sports Sciences, 2024)
Prior studies have shown that experts possess an excellent ability for action anticipation. However, it is not clear how experts process the discrepancies between predicted outcomes and actual outcomes. Based on Bayesian theory, Experiment 1 in the current study explored this question by categorizing unexpected outcomes into gradually increasing discrepancies and comparing the performance of experts and novices on a congruence discrimination task. Our behavioral analysis revealed that experts outperformed novices significantly in detecting these discrepancies. The following electroencephalogram study in Experiment 2 was conducted focused exclusively on experts to examine the role of theta wave oscillations within the mid-frontal cortex in processing varying levels of discrepancy. The results showed that reaction time and theta oscillations gradually increased as the magnitude of discrepancy increased. These findings indicate that compared to the novices, experts have a better ability to perceptual the discrepancy. Also, the magnitude of discrepancies induced an increase in mid-frontal theta in experts, providing greater flexibility in their response strategies.